Corona Virus Disease (Covid-19) Social Impact Analysis In Bekasi City - Fadhillah , Muhammad; Purnamasari , Ranty; Haskara , Muhammad; Firdaus , Imansyah; Suhendra , Adi (Universitas Muhammadiyah Yogyakarta, 2023)
The COVID-19 pandemic has had a tremendous impact around the world. The impact that occurs is not only in the economic field, but also in the social field. Research on the social impact of COVID-19 can assist in formulating the necessary policies more effectively. This study uses qualitative research methods with primary data collection by survey and secondary data collection through the relevant agencies. The results of this study explain the analysis of social impacts arising from the COVID-19 Pandemic as seen from the impact on individuals, workers, poverty, families, security, and society. Based on the survey results, COVID-19 against individuals, in a response of shock, disbelief and frustration. The Covid-19 pandemic in the city of Bekasi forced restrictions on activities outside the home to stop the economy and lead to layoffs, a decrease in income which led to the potential for new poor people to be born, conflicts in the family and an increase in crime. However, in the community structure of Bekasi City, this outbreak can also shape mutual cooperation behavior in caring for the prevention of the spread of COVID-19.